Framing of Women in Politics: A case of Pakistani Elections 2013 - Bushra Hameedur Rahman; Abida Eijaz; Rana Eijaz Ahmad (Journal of Political Studies, 2015)
This paper is a content analysis of four major dailies and two political talk shows on the two leading TV news channels of Pakistan during the 2013 Elections. The study examines whether women in politics were portrayed marginally or as active agents in the political process. The paper examines if women were framed by stereotypes and whether they were taken seriously or simply as sensational tokens. Whether during the election campaign they were encouraged to come into politics and for voting? Findings show that the coverage given to women was minimal, and they were not represented as politicians with vision and contributors in political decision making. However, female politicians did not suffer from the cultural stereotype treatment in the news items. In the comparative analysis between Urdu and English dailies, English dailies coverage on women political participation was greater and more positive than Urdu dailies.